Sunbelt/frostbelt : public policies and market forces in metropolitan development - Pack, Janet Rothenberg (Washington, D.C. : Brookings Institution Press, 2005)
"The product of a multiyear project looking at how government policies shape growth patterns in five metropolitan areas--Los Angeles, Phoenix, Pittsburgh, Chicago, and Philadelphia--this book examines how these sunbelt and frostbelt metro areas have tried to use policy reform to address their individual development challenges"--Provided by publisher
Metropolitan development : patterns, problems, causes, policy proposals / Janet Rothenberg Pack -- Chicago : metropolitan decentralization / Wim Wiewel, Joseph Persky, and Kimberly Schaffer -- Los Angeles : region by design / Jennifer Wolch [and others] -- Philadelphia : spatial economic disparities / Joseph Gyourko and Anita A. Summers -- Phoenix : dealing with fast growth / Arizona State University Research Team -- Pittsburgh : economic restructuring and regional development patterns, 1880-2000 / Robert E. Gleeson and Jerry Paytas.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Metropolitan areas -- United States; Metropolitan areas -- Government policy -- United States; Regional planning -- United States; Cities and towns -- United States -- Growth; Aménagement du territoire -- États-Unis.; Villes -- États-Unis -- Croissance; SOCIAL SCIENCE -- Sociology -- Urban; BUSINESS & ECONOMICS -- Urban & Regional; Cities and towns -- Growth; Metropolitan areas; Metropolitan areas -- Government policy; Regional planning; United States